Fifth stage pharmacy students’ knowledge and perceptions about generic medicines - Dheyaa J. Kadhim; Fajir I. Ahmed; Ronak A. Hussein (International Journal of Research in Pharmaceutical Sciences, 2020)
The aim of the current study was to evaluate the knowledge and perception of the fifth stage pharmacy students (college of pharmacy/ University of Baghdad /Iraq) regarding generic medicines. This study is a cross-sectional study carried in a college of pharmacy /University of Baghdad during the period from (November 2018- March 2019). The number of students included in the current study was 168 undergraduate stager pharmacists. A questionnaire was used to collect data of the study. Nearly 86% of the students said that they had heard of generic and brand medicines, and pharmacy was the main source of knowledge regarding generic medicines (66.7%). About (33.3%) of the respondents agreed that generic medicines are bioequivalent to brand medicine. However, (38.1%) perceived generic medicines might not be the therapeutic equivalent of brand medicines. In addition, (35.1%) of the respondents believed that generics are lower in quality, which is why they are cheap and produce more side effects. Moreover, (41.1%) of the sample agreed that generic medicines should be avoided in life-threating situations. About (56.5 %) of the students were found to have a poor level of perception regarding the use of generic medicines. The majority of the fifth stage pharmacy students (college of pharmacy/ University of Baghdad /Iraq) were found to have a good knowledge but a poor level of perception about the use of generic medicines.